PENGARUH METODEL ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA DI SDN 33 PONTIANAK UTARA - Siregar, Ernawati; Marzuki, Marzuki; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract.From the results of interviews at North Pontianak Public Elementary School 33, it is known that speaking skills of VA class students are still below the completeness standard, that is there are 17 students from 28 students who have not yet completed the aspect of speaking. Inner problem this research is